2006
DOI: 10.1016/j.cellbi.2006.01.004
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐Dihydroxyvitamin D3 inhibits tumor necrosis factor‐α‐induced adhesion molecule expression in endothelial cells

Abstract: This study tested the hypothesis that 1,25-dihydroxyvitamin D(3) [1,25(OH)(2)D(3)] plays a role in human umbilical vein endothelial cells (HUVEC) cultures. HUVEC were incubated with 10 or 100 nM 1,25(OH)(2)D(3) for 24 h, in the absence or presence of 40 ng/ml tumor necrosis factor-alpha (TNF-alpha) or 2 ng/ml interleukin-1alpha (IL-1alpha). 1,25(OH)(2)D(3) did not affect HUVEC viability and proliferation, while TNF-alpha, alone or in combination with the hormone, significantly inhibited HUVEC viability. [(3)H]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 44 publications
(47 reference statements)
7
56
1
2
Order By: Relevance
“…Our results are surprising given the available biologic evidence supporting a role for vitamin D in modulating vascular function. This evidentiary trail includes in vitro findings of vitamin D receptors on human endothelial cells, the ability of active vitamin D to inhibit the expression of adhesion molecules on these cells, 24,25 and in vivo studies in animals demonstrating reductions of blood pressure and endothelial-dependent contractions in spontaneously hypertensive rats treated chronically with vitamin D. 26,27 Additionally, recent observational and small interventional trials have linked low vitamin D status to poor vascular health, 28 and vitamin D sufficiency or repletion to improvement in brachial artery flow-mediated vasodilatation (FMD), reactive hyperemia index, aortic stiffness, and blood pressure. [28][29][30] These studies, however, were crosssectional/observational, 28 non-randomized, and included only healthy asymptomatic subjects 29 and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are surprising given the available biologic evidence supporting a role for vitamin D in modulating vascular function. This evidentiary trail includes in vitro findings of vitamin D receptors on human endothelial cells, the ability of active vitamin D to inhibit the expression of adhesion molecules on these cells, 24,25 and in vivo studies in animals demonstrating reductions of blood pressure and endothelial-dependent contractions in spontaneously hypertensive rats treated chronically with vitamin D. 26,27 Additionally, recent observational and small interventional trials have linked low vitamin D status to poor vascular health, 28 and vitamin D sufficiency or repletion to improvement in brachial artery flow-mediated vasodilatation (FMD), reactive hyperemia index, aortic stiffness, and blood pressure. [28][29][30] These studies, however, were crosssectional/observational, 28 non-randomized, and included only healthy asymptomatic subjects 29 and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with end-stage renal disease, calcidiol and calcitriol levels are inversely correlated with atherosclerosis and endothelial dysfunction (66). Furthermore, VDRAs downregulate LPS-induced immune activation of endothelial cells (28) and inhibit TNF-␣-induced adhesion molecules expression in cultured endothelial cells (71). Mice lacking VDRs show lower platelet aggregation and higher fibrin formation in the liver and kidney after LPS administration (2), suggesting an important role for VDRA on endothelial dysfunction.…”
Section: Role Of Vdra In the Vasculaturementioning
confidence: 99%
“…31 In human umbilical vein endothelial cells, the increase of VCAM-1 and ICAM-1 induced by TNF-a were inhibited by 1a,25-(OH) 2 D 3 . 32 The present study first showed that the active form of vitamin D directly influences BBB endothelial cells through the upregulation of tight junction proteins and downregulation of cell adhesion molecules under TNF-a stimulation. We incubated 1a,25-(OH) 2 [36][37][38][39] In the present study, we observed that 1a,25-(OH) 2 D 3 restored the decrease of claudin-5 and ZO-1 in the cells induced by RRMS sera.…”
Section: Discussionmentioning
confidence: 99%